2015
DOI: 10.1111/jnu.12123
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of U.S. Nursing Faculty in Research‐ and Practice‐Focused Doctoral Education

Abstract: The Institute of Medicine has recommended doubling the number of doctorally prepared nurses in the United States by 2020 to ensure that sufficient numbers of faculty are available to prepare the nursing labor force that is needed for delivery of healthcare services. Nurse scientists are needed to contribute to improvement in patient care quality and safety, and practice leaders are needed to facilitate the translation of research into safe, high-quality, and cost-effective care. The landscape of doctoral educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…Nursing's distinctive historical trajectory has brought us to the brink of a current crisis in which there are too few doctorally prepared nurses internationally to fill university faculty vacancies, let alone the emerging opportunities for nursing scholarship in various research, leadership and health policy positions toward which the wisdom of our discipline would be ideally suited (American Association of Colleges of Nursing, ; Oermann, Lynn, & Agger, ). While we have witnessed a global proliferation of degree‐granting at the doctoral level, a significant proportion of that now occurs in the form of professional doctorates and at academic institutions not yet well suited to the support of a robust research and knowledge generation training environment (Institute of Medicine, ; Kim, Park, Park, Khan, & Ketefian, ; McKenna, Keeney, Kim, & Park, ; Smeltzer et al., ). Adding another layer of complication, an increasing number of research‐intensive academic nursing programs are focusing their PhD curricula on research methods training, and reducing the emphasis that would traditionally have been placed on such elements as the history of theoretical thinking in nursing, and philosophy of science from the perspective of our distinctive applied discipline (Regh & SmithBattle, ; Wyman & Henly, ).…”
mentioning
confidence: 99%
“…Nursing's distinctive historical trajectory has brought us to the brink of a current crisis in which there are too few doctorally prepared nurses internationally to fill university faculty vacancies, let alone the emerging opportunities for nursing scholarship in various research, leadership and health policy positions toward which the wisdom of our discipline would be ideally suited (American Association of Colleges of Nursing, ; Oermann, Lynn, & Agger, ). While we have witnessed a global proliferation of degree‐granting at the doctoral level, a significant proportion of that now occurs in the form of professional doctorates and at academic institutions not yet well suited to the support of a robust research and knowledge generation training environment (Institute of Medicine, ; Kim, Park, Park, Khan, & Ketefian, ; McKenna, Keeney, Kim, & Park, ; Smeltzer et al., ). Adding another layer of complication, an increasing number of research‐intensive academic nursing programs are focusing their PhD curricula on research methods training, and reducing the emphasis that would traditionally have been placed on such elements as the history of theoretical thinking in nursing, and philosophy of science from the perspective of our distinctive applied discipline (Regh & SmithBattle, ; Wyman & Henly, ).…”
mentioning
confidence: 99%
“…DNP graduates account for most of this growth. Smeltzer et al (2015) reported increasing numbers of DNP graduates in faculty positions and that these faculty were more likely to be engaged in evidence-based clinical practice improvement projects focused on the care of older adults than research studies (Smeltzer et al, 2015). The likelihood that DNP-prepared gerontological nursing faculty will be expected to move their work into funded research indicates a niche for peer mentoring in which more established DNP and research faculty serve as part of a mentoring team invested in the academic success of the novice faculty member.…”
Section: Discussionmentioning
confidence: 99%
“…The number of research-focused doctoral programs increased 65% between 2001 ( n = 86) and 2010 ( n = 133), intensifying the demand for research-savvy faculty (Kim, Park, Park, Khan, & Ketefian, 2014). The nursing faculty shortage was exacerbated by growth in practice-focused doctoral education that dramatically outpaced research-focused education (Smeltzer et al, 2015), thus further affecting the number of faculty prepared to mentor fledgling researchers. In 2014, there were only 3,065 students enrolled in 134 PhD programs in comparison with 18,352 students enrolled in 264 DNP programs (AACN, 2015; Broome and Corazzini 2016).…”
Section: The Impact Of the Robert Wood Johnson Foundation’s Nurse Facmentioning
confidence: 99%